Abdullah Thatha Sonna Puthirkkathaikal - Balabharathi, Yes; Pillai (Trichy : S. R. V. Tamil Publishing House, 2023)
"How fun would it be to give your brain a workout? Here, Grandpa Abdullah is waiting with plenty of puzzles to entertain you."--Back cover.
Keywords: Curiosities and wonders; Questions and answers